-v/6=-47

Simple and best practice solution for -v/6=-47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -v/6=-47 equation:



-v/6=-47
We move all terms to the left:
-v/6-(-47)=0
We add all the numbers together, and all the variables
-v/6+47=0
We multiply all the terms by the denominator
-v+47*6=0
We add all the numbers together, and all the variables
-1v+282=0
We move all terms containing v to the left, all other terms to the right
-v=-282
v=-282/-1
v=+282

See similar equations:

| -12=4(x-6) | | 20=x/20 | | -3x+8=-2+9x | | x/4-16=10 | | -11y-6=11-8y | | 4(-x+1)+3=-2(x+1) | | 5w+15=105 | | -11y-6=2-8y | | 15x+2=10x+23 | | (2)1-x=5 | | -5(8n+6)=36+7n | | -92=-8+2(6x+6) | | (4)1-x=5 | | 0(2y+2)−y=2(8y−8) | | 7(-3b+3)=-8+8b | | m∠1+117+33=180 | | 12x+7×=312 | | 4(1/3x+8)=12x | | 0=(2x)(24-2x)(18-2x) | | 1.6/1=y/1.6 | | (x-3)(x+4)-18=0 | | b/4+4=20 | | 2x-2x+4=6 | | D=(-7/5)t+22 | | 3x-7x=-4+5-11 | | -2(-v2)=-3-2v | | 3x/4+7x/8=36 | | 3x+5x=100 | | Y2-16x=0 | | 3x+11=16x= | | 2-3x-4=4 | | 9y+2+2y+3+15y-27=180 |

Equations solver categories